1995
DOI: 10.1523/jneurosci.15-02-01567.1995
|View full text |Cite
|
Sign up to set email alerts
|

TrkA expression in the CNS: evidence for the existence of several novel NGF-responsive CNS neurons

Abstract: NGF acts as a neurotrophic factor by binding and activating its receptor on certain neuronal populations in the CNS and PNS. TrkA is a receptor for NGF. Recent findings in vitro indicate that this NGF- activated receptor tyrosine kinase transduces the NGF signal. To further define NGF actions in the CNS, we examined trkA expression in the adult rat brain. We found that trkA mRNA and immunoreactivity (IR) coincided in specific, defined neuronal populations in the forebrain and brainstem. In addition to choliner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
89
0
3

Year Published

1996
1996
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(104 citation statements)
references
References 65 publications
12
89
0
3
Order By: Relevance
“…Immunostaining for NGF within the infusion site showed that exogenous NGF was con¢ned mainly to the cortical neuropil and seemed to avoid cortical neuronal cell bodies. We did not observe any TrkA immunoreactivity in cortical neurons (data not shown), and this is in agreement with other studies (Sobreviela et al, 1994;Holtzman et al, 1995). In addition, Domenici et al (1994b) found that the number of basal forebrain neurons labeled by a local injection of radiolabeled NGF into rat occipital cortex was one to two orders of magnitude greater than the number of labeled cortical neurons near the injection site, depending on the age of the animal.…”
Section: Possible Actions Of Ngf On Cortical Neuronssupporting
confidence: 92%
“…Immunostaining for NGF within the infusion site showed that exogenous NGF was con¢ned mainly to the cortical neuropil and seemed to avoid cortical neuronal cell bodies. We did not observe any TrkA immunoreactivity in cortical neurons (data not shown), and this is in agreement with other studies (Sobreviela et al, 1994;Holtzman et al, 1995). In addition, Domenici et al (1994b) found that the number of basal forebrain neurons labeled by a local injection of radiolabeled NGF into rat occipital cortex was one to two orders of magnitude greater than the number of labeled cortical neurons near the injection site, depending on the age of the animal.…”
Section: Possible Actions Of Ngf On Cortical Neuronssupporting
confidence: 92%
“…This effect is likely mediated by activation of cortical TrkA, since the specific TrkA-activating antibody RTA also rescues LGN neurons from monocular deprivation-induced shrinkage (T. Pizzorusso, N. B. and L. M., unpublished) and prevents monocular deprivation effects in visual cortex . TrkA is not expressed by LGN neurons (Merlio et al, 1992;Holtzman et al, 1995), and LGN neurons do not retrogradely transport cortically infused NGF or RTA Pizzorusso et al, 1999). Rather, TrkA is expressed by cholinergic afferents (Merlio et al, 1992;Sobreviela et al, 1994;Holtzman et al, 1995;Rossi et al, 2002) and some cortical glutamatergic terminals (Sala et al, 1998).…”
Section: Ngf Accelerates Lgn Developmentmentioning
confidence: 99%
“…Expression of trkA in sympathetic neurons starts at E13.5 and reaches highest levels at E18, coinciding with the time of their maximum response to NGF (Ernfors et al, 1992). In the central nervous system trkA mRNA has been found in NGFresponsive cholinergic neurons of the basal forebrain and neostriatum and in some non-cholinergic neurons in several nuclei at di erent regions of the brainstem (Holtzman et al, 1995). trkA expressing neurons closely match those that are NGF-dependent for survival and di erentiation, suggesting that trkA could mediate NGF actions in vivo.…”
mentioning
confidence: 98%